Genotypic diversity and molecular characterization of DENV-2 in a Peruvian endemic region from 2016 to 2022: displacement of American/Asian genotype - Tarazona-Castro, Yordi; Aguilar-Luis, Miguel Angel; Silva-Caso, Wilmer; Watson, Hugh; Zavaleta-Gavidia, Victor; Aquino-Ortega, Ronald; Del Valle, Luis J.; Bazan-Mayra, Jorge; Mayta Huatuco, Egma; del Valle-Mendoza, Juana (Frontiers in Microbiology, 2025)
BackgroundDengue is the most prevalent acute febrile disease with serious clinical consequences in the tropical and subtropical regions of Asia and America. In Peru, it represents a significant public health issue due to its hyperendemic nature, with serotype 2 (DENV-2) being the predominant serotype that leads to the most severe clinical manifestations of the disease. This study focuses on the molecular characterization and analysis of the intraserotypic diversity of DENV-2 circulating in the endemic region of Cajamarca.MethodsA total of 3,967 blood serum samples from patients with acute febrile illness (AFI) were analyzed between 2016 and 2022 to detect DENV and DENV-2 using real-time RT-PCR. The viral envelope (E) gene was then sequenced using the Sanger method. Finally, phylogenetic reconstruction was conducted using the maximum likelihood method.ResultsA total of 32 complete sequences of the envelope gene were obtained, and the phylogenetic and characterization analyses of the amino acid sequences revealed that, during the period from 2016 to 2022, two DENV-2 genotypes circulated: the Am/As genotype and the cosmopolitan genotype in lineages 2 and C, respectively.ConclusionSimilarly, our findings showed that every studied outbreak was characterized by novel autochthonous variants of the Am/As genotype and by an imported variant of the cosmopolitan genotype; this demonstrates a temporal distribution of intraserotypic variability that indicates the displacement of the Am/As genotype around 2021 and the establishment of the cosmopolitan genotype. The need for ongoing genetic or genomic surveillance of the cosmopolitan virus arises in order to understand its distribution and diversification patterns in Peru.